Parental attitude and knowledge towards asthma care measures for their children in Saudi Arabia. Issue 11 (17th September 2020) - Alhammad, Abdullah M.; Alajmi, Ghada; Alenizi, Ahmed; Alrashidi, Essa; Alghannam, Ghannam; Alaki, Emadia; Alsaadi, Muslim M; Mayet, Ahmed Y.
Abstract: Background: Appropriate asthma management in children reduces emergency department visits, hospitalization, and improves the quality of life. We aim to assess the level of children asthma control and its association with parental knowledge. Methods: A prospective study conducted to measure childhood asthma control with a validated childhood asthma control test (C‐ACT), and to assess asthma knowledge among the parents of children aged 4–11 years and their parents upon asthma clinic visits. C‐ACT score ≤ 19 is considered as uncontrolled child asthma. Results: We have invited 238 parents to participate in the study; 177 (74.4%) completed the survey. The mean age of the parents and their children were 38.8 ± 7.6 and 7.8 ± 2.7 years, respectively; 28.2% of parents were smokers, and 46.3% of them were college graduated. Nearly 61.6% of the parents and children scored ≤ 19 on C‐ACT; 54.2% and 37.9% of parents knew how inhaled salbutamol and corticosteroids work, respectively. A quarter of the parents received an asthma action plan. Multinomial logistic regression analysis showed that parents who did not know their children's medications name (OR, 6.1; 95% CI, 2.15–17.29), and when to use inhaled corticosteroid (OR, 2.1; 95% CI, 1.32–3.45) were independent factors predicting uncontrolled asthma in children with score ≤ 19. Conclusions: The study indicated that there is an association between poor asthma control (scored ≤ 19 on C‐ACT) and parental knowledge of asthma medications. The parents should be educated thoroughly on asthma care, including medications used to minimize asthma exacerbations in their children.